Women Reshaping Human Rights: How Extraordinary Activists Are Changing the World - Bouvard, Marguerite Guzman (Rowman & Littlefield Publishers, 1996)
In Women Reshaping Human Rights ,ordinary yet extraordinary women tell their stories, in their own words. Their deeds span continents and have profoundly affected millions worldwide.Readers will meet Vera Laska, who as a teenager joined the resistance against the Nazis in Czechoslovakia; Dai Qing, who fights the Communist Party's grip upon the media and government in the People's Republic of China; and Juana Beatrice Gutierrez and the Mothers of East Los Angeles, who challenge drug dealers and toxic polluters threatening their neighborhood. Professor Bouvard provides a complete biography of every activist. The stage is thus set for each individual, who recounts real-life stories of courage that sadly until now have gone unnoticed. Finally we hear the voices of those who have transformed the quest for human rights. This volume is divided into five sections: Confronting Authoritarian Governments, Struggling with Race and Ethnicity, Seeking Enviromental Justice, Upholding Women's Rights as Human Rights, and Making the World Safe for Childern.